2007
DOI: 10.1590/s0100-40422007000500009
|View full text |Cite
|
Sign up to set email alerts
|

Clerodane diterpenes from leaves of Casearia sylvestris Swartz

Abstract: Recebido em 18/4/06; aceito em 10/11/06; publicado na web em 17/7/07Ethanolic extracts of the leaves of Casearia sylvestris yielded a novel clerodane diterpene, 15-hydroxy-3-cleroden-2-one, together with the known diterpenes (-)-hardwickiic acid, reported for the first time from this species, and casearins B and G, previously isolated from C. sylvestris. The structures of all four compounds were determined by spectrometric analysis. The new clerodane diterpene and (-)-hardwickiic acid contain structural featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 14 publications
1
29
0
2
Order By: Relevance
“…1). The diacetalic ring is a highly oxygenated structure rarely seen in natural molecules, being a protected dialdehyde (Santos et al 2007). Bioguided fractionation assays have regularly revealed that clerodane diterpenes, predominantly those rich in oxygen atoms, possess antifungal, antibacterial, insecticidal, antifeedant and cytotoxic properties (Morita et al 1991, Merrit and Ley 1992, Oberlies et al 2002, Vieira-Junior et al 2009).…”
Section: Antitumor Activitymentioning
confidence: 99%
“…1). The diacetalic ring is a highly oxygenated structure rarely seen in natural molecules, being a protected dialdehyde (Santos et al 2007). Bioguided fractionation assays have regularly revealed that clerodane diterpenes, predominantly those rich in oxygen atoms, possess antifungal, antibacterial, insecticidal, antifeedant and cytotoxic properties (Morita et al 1991, Merrit and Ley 1992, Oberlies et al 2002, Vieira-Junior et al 2009).…”
Section: Antitumor Activitymentioning
confidence: 99%
“…19 The structures of 3 and 4 were identified by NMR as patagonic acid 14 and (4aR,5S,6R,8aR)-5-[2-(2,5-dihydro-5-methoxy-2-oxofuran-3-yl)ethyl]-3,4,4a,5,6,7,8,8a-octahydro-5,6,8a-trimethylnaphthalene-1-carboxylic acid, respectively, both diterpenes of the clerodane type. 15,24,25 According to the literature 14 on substance 3 the chemical shifts of C-2 is 27.4 and C-7 is 27.2. HMBC spectrum showed a correlation of the signal at 0.85 (d, J 6.7 Hz, CH 3 -17) with the signal at 27.2, being this signal assigned to C-7, and a correlation of the signal at 6.81 (br s H-3) with the signal at 27.4, which was assigned to C-2.…”
Section: Resultsmentioning
confidence: 99%
“…4,5) Many diterpenoids were reported from the C. sylvestris with antitumoral, trypanocidal and DNA-modifying bioactivities. [6][7][8][9][10][11][12] In continuation of our program to search for new chemical and bio-marker of the dietary supplement, the present paper described the separation and structure elucidation of two new C 13 nor-isoprene glycosides, (6S,9S)-6,9-dihydroxymegastiman-4-en-9-O-b-D-glucopyranoside (1) and (6S,9S)-6,9-dihydroxymegastiman-4-en-9-O-b -D-apiofuranosyl-(1→6)-b -D-glucopyranoside (2) from the leaves of C. sylvestris, together with four known C 13 nor-isoprenoids, namely, icariside B 5 (3), 13) byzantionoside B (4), 14) blumenol B (5) and blumenol C (6), 15,16) and one known C 11 nor-isoprene loliolide (7).17) All these compounds were reported for the first time from the title plant. Their structures ( 13) which was obtainted from the same subfraction at different retention time by preparative HPLC method.…”
mentioning
confidence: 99%